The medium-term impact of the primary education stipend in rural Bangladesh - Baulch, Bob (International Food Policy Research Institute, 2010)
This series of notes summarizes findings of a project entitled “What development interventions work?” undertaken by researchers of the Chronic Poverty Research Centre, the International Food Policy Research Institute, and Data Analysis and Technical Assistance Ltd. As part of a larger longitudinal study that resurveyed 1,907 households and 102 villages in 14 of Bangladesh's 64 districts, the project focused on assessing the long-term impacts of a number of anti-poverty interventions—specifically, microfinance, agricultural technology, and educational transfers— on a range of monetary and nonmonetary measures of well-being. This note focuses on the long-term impacts on men's and women's assets of disseminating agricultural technologies to individuals compared with groups. It is hoped that these results will help policymakers, donors, and other stakeholders to effectively evaluate different interventions thereby contributing to the design of future anti-poverty programs in South Asia.The Primary Education Stipend (PES) program aims to increase school enrollments and attainments by providing cash incentives for poor parents to send their children to school. Households with qualifying pupils who attend school 85 percent of the time receive 100 Taka (Tk) per month for one child (about US$1.76) and Tk 125 per month for more than one child. To qualify for the program, children must be of primary school age and meet at least one of the following five eligibility criteria: 1. Belong to a landless or near landless household (one that owns less than half an acre of land) 2. Have parents who work as day laborers 3. Belong to a female-headed household (one where the head is widowed, separated, or divorced or where the husband is disabled) 4. Belong to a household that derives its living from fishing, pottery, weaving, blacksmithing, or cobbling) 5. Belong to a household that derives its living from sharecropping